2007
DOI: 10.1128/aem.01608-06
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Level Regulation of Genes for Protocatechuate Degradation in Acinetobacter baylyi Includes Cross-Regulation

Abstract: The bacterium Acinetobacter baylyi uses the branched ␤-ketoadipate pathway to metabolize aromatic compounds. Here, the multiple-level regulation of expression of the pca-qui operon encoding the enzymes for protocatechuate and quinate degradation was studied. It is shown that both activities of the IclR-type regulator protein PcaU at the structural gene promoter pcaIp, namely protocatechuate-dependent activation of pca-qui operon expression as well as repression in the absence of protocatechuate, can be observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 38 publications
4
35
0
Order By: Relevance
“…The pcaUp promoter, which controls the expression of the pcaU regulatory gene belonging to the IclR family, is also subject to catabolic repression, but the molecular mechanism remains unknown (Dal et al, 2002;Siehler et al, 2007). Taking our results together with previous data (Torres et al, 2003) we have demonstrated that the glucose effect on mhp expression is exerted at the level of both catabolic and regulatory promoters.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The pcaUp promoter, which controls the expression of the pcaU regulatory gene belonging to the IclR family, is also subject to catabolic repression, but the molecular mechanism remains unknown (Dal et al, 2002;Siehler et al, 2007). Taking our results together with previous data (Torres et al, 2003) we have demonstrated that the glucose effect on mhp expression is exerted at the level of both catabolic and regulatory promoters.…”
Section: Discussionsupporting
confidence: 64%
“…The pcaUp promoter, which controls the expression of the pcaU regulatory gene belonging to the IclR family, is also subject to catabolic repression, but the molecular mechanism remains unknown (Dal et al, 2002;Siehler et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Thus the differential expression on the noninducing carbon sources investigated here is independent of the induction status, an observation that had been made earlier for the pca-qui operon (Siehler et al, 2007;Trautwein & Gerischer, 2001). …”
Section: The Dca Genes Underlie Catabolite Repressionmentioning
confidence: 64%
“…Since a strong catabolite repression of the pca operon has been shown (Dal et al, 2002;Siehler et al, 2007) we address here the question if other operons linked with aromatic compound catabolism (are, ant, ben, hca, dca) also underlie this regulatory mechanism. To answer this question we produced transcriptional fusions between the catabolic genes and the luc gene, coding for luciferase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation